Analisis Pola Spasial Kejadian Tawuran Remaja Periode 2019-2023 - Aliyatul Maghfiroh; Siti Dahlia; Agung Adiputra; Tricahyono Nur Harsono (Jurnal Penelitian Pendidikan Geografi, 2025)
Tebet District, South Jakarta has been the location of several incidents of juvenile brawls recorded in recent years. There was a clash between two groups of teenagers on Jalan Dr. Saharjo Tebet in 2019 which caused traffic jam due to stone throwing at each other. The objectives of this study are 1) to analyze the spatial pattern of adolescent brawls from 2019 to 2023; 2) to identify factors that affect changes in the pattern of adolescent brawls in Tebet District. The method used is Nearest Neighbor Analysis by utilizing the Geographic Information System. The data collection techniques used are observation, interviews and documentation. The results of the study show that there are 2 main roads, namely Jalan KH. Abdullah Syafei and Jalan Dr. Saharjo which is the location where teenage brawls often occur. Over the last 5 years, the distribution pattern of brawl points has shown a random pattern. The factors that affect the change in the spatial pattern of the location of juvenile brawls are the increase in security patrols and the perpetrators are teenagers from other villages. The analysis shows that each year does not experience a very different shift.